Apatinib induces 3‐hydroxybutyric acid production in the liver of mice by peroxisome proliferator‐activated receptor α activation to aid its antitumor effect. Issue 10 (5th September 2019) - Feng, Siqi; Wang, Huan; Wang, Ying; Sun, Runbin; Xie, Yuan; Zhou, Zhu; Wang, Hong; Aa, Jiye; Zhou, Fang; Wang, Guangji
Abstract: Apatinib, an antiangiogenic agent, shows efficient antitumor activity in a broad range of malignancies. Considering tumor is a type of metabolic disease, we investigated the metabolomics changes in serum and tumor after apatinib treatment and the molecular mechanism of characteristic changes associated with its antitumor efficacy. Molecules in serum and tumor tissue were extracted and analyzed by a gas chromatography‐mass spectrometry metabolic platform. Apatinib significantly inhibited e tumor growth and alleviated metabolic rearrangement in both serum and tumor of A549 xenograft mice. Among these endogenous metabolites, 3‐hydroxybutyric acid (3‐HB) was significantly increased in serum, tumor and liver after apatinib treatment. Interestingly, giving exogenous 3‐HB also inhibited tumor growth. Gene expression, dual luciferase reporter gene assay and molecular docking analysis all indicated that apatinib could induce 3‐HB production through the dependent activation of peroxisome proliferator‐activated receptor α (PPARα) and promotion of fatty acid utilization in the liver. Therefore, increased content of 3‐HB induced by PPARα activation in the liver partially contributed to the antitumor effect of apatinib. It may provide clues to another potential mechanism underlying the antitumor effect of apatinib besides its antiangiogenic effect through inhibiting vascular endothelial growth factor receptor 2. Abstract : Apatinib significantly alleviated metabolic rearrangement in both serum and tumor of A549 xenograft mice. Apatinib regulated fatty acid metabolism and 3‐hydroxybutyric acid production by activation of PPARα in the liver of A549 xenograft mice. Increased content of 3‐hydroxybutyric acid partially contributed to the antitumor effect of apatinib.